2012
DOI: 10.1007/s10555-012-9351-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell–cell and cell–matrix dynamics in intraperitoneal cancer metastasis

Abstract: The peritoneal metastatic route of cancer dissemination is shared by cancers of the ovary and gastrointestinal tract. Once initiated, peritoneal metastasis typically proceeds rapidly in a feed-forward manner. Several factors contribute to this efficient progression. In peritoneal metastasis, cancer cells exfoliate into the peritoneal fluid and spread locally, transported by peritoneal fluid. Inflammatory cytokines released by tumor and immune cells compromise the protective, anti-adhesive mesothelial cell laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(168 citation statements)
references
References 160 publications
(214 reference statements)
4
163
1
Order By: Relevance
“…This mesothelial layer is highly receptive to ovarian cancer seeding [66]. Implantation of spheroids on the peritoneum involves interactions between cancer cells and the mesothelium.…”
Section: How Does the Tumor Environment Afect Eoc Dissemination?mentioning
confidence: 99%
“…This mesothelial layer is highly receptive to ovarian cancer seeding [66]. Implantation of spheroids on the peritoneum involves interactions between cancer cells and the mesothelium.…”
Section: How Does the Tumor Environment Afect Eoc Dissemination?mentioning
confidence: 99%
“…The three-dimensional tumor spheroid model has been suggested to represent an in vitro system similar to that of micrometastases [26]. In fact, it has been suggested that certain cancers utilize endogenous spheroid formation to survive transit through the peritoneal cavity to sites of metastasis [18]. In addition, recent studies have shown that metastases require the support of stromal cells for continuous growth and propagation [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor spheroids mimic the structure of metastatic lesions and are more relevant for assessing drug delivery than monolayer cultures [17,18]. We have shown previously that human serum albumin (HSA) nanoconjugates with multiple arginine-glycine-aspartic acid (RGD) peptides are able to effectively penetrate and distribute in a tumor spheroid model [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have indicated that exosomes derived from cancer cells cause the proliferation and transformation of PMCs [56]. In the process of peritoneal metastasis, normal PMCs become carcinoma-associated fibroblasts.…”
Section: The Potential Relevance Between Exosomes and Pmcsmentioning
confidence: 99%